2012
DOI: 10.1073/pnas.1211850110
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the local tumor microenvironment in recurrent cancers may explain the failure of vaccines after surgery

Abstract: Each year, more than 700,000 people undergo cancer surgery in the United States. However, more than 40% of those patients develop recurrences and have a poor outcome. Traditionally, the medical community has assumed that recurrent tumors arise from selected tumor clones that are refractory to therapy. However, we found that tumor cells have few phenotypical differences after surgery. Thus, we propose an alternative explanation for the resistance of recurrent tumors. Surgery promotes inhibitory factors that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(154 citation statements)
references
References 31 publications
8
146
0
Order By: Relevance
“…To do so, we obtained pleural effusion cells from patients with stage IV NSCLC to check the mRNA levels of IRF5 and M-CSF in EpCAM þ epithelial cells. We also analyzed total numbers of CSF1R-positive macrophages in NSCLC tumors, which have been known as tumorigenic and immunosuppressive subsets in human cancers (20,21). We found that mRNA levels of IRF5 were highly correlated with those of M-CSF in tumor tissues in patients with NSCLC (Fig.…”
Section: Clinical Significance Of Irf5-m-csf Pathwaysmentioning
confidence: 90%
“…To do so, we obtained pleural effusion cells from patients with stage IV NSCLC to check the mRNA levels of IRF5 and M-CSF in EpCAM þ epithelial cells. We also analyzed total numbers of CSF1R-positive macrophages in NSCLC tumors, which have been known as tumorigenic and immunosuppressive subsets in human cancers (20,21). We found that mRNA levels of IRF5 were highly correlated with those of M-CSF in tumor tissues in patients with NSCLC (Fig.…”
Section: Clinical Significance Of Irf5-m-csf Pathwaysmentioning
confidence: 90%
“…Combination treatment with the anti-CD4 mAb and various immune checkpoint mAbs, particularly anti-PD-1 and anti-PD-L1 mAbs, revealed striking synergy in suppressing tumor growth and prolonging survival. Several previous reports have described antitumor activity of anti-CD4 mAb treatment in solid tumor models in C57BL/6 mice, including subcutaneous tumors induced by inoculation with B16 melanoma cells (9,11,12), recurrent TC1 lung cancer cells (30), or embryo cells expressing the adenovirus-derived E1A protein (10). Although the efficacy of immunotherapy in mouse tumor anti-CD4, anti-PD-L1, anti-PD-1 or anti-CD8 mAbs or a combination of these according to the treatment schedule shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Five micrometer-thick sections from tissue biopsies obtained during the surgery were mounted with a glycerin-based mounting media and frozen tumor sections were prepared as previously described. 29 The samples were examined using an Olympus ® IX51 fluorescent microscope equipped with an ICG specific filter set (Chroma ® 49030). Fluorescence images were acquired using a PixeLink ® NIR CCD camera (PL-B741EU).…”
Section: Histopathology and Fluorescence Microscopymentioning
confidence: 99%